Genome-wide association study unravels mechanisms of brain glymphatic activity - Huang, Shu-Yi; Ge, Yi-Jun; Ren, Peng; Wu, Bang-Sheng; Gong, Weikang; Du, Jing; Chen, Shi-Dong; Kang, Ju-Jiao; Ma, Qing; Bokde, Arun L. W.; Desrivières, Sylvane; Garavan, Hugh; et al. (Nature Communications, 2025)
Brain glymphatic activity, as indicated by diffusion-tensor imaging analysis along the perivascular space (ALPS) index, is involved in developmental neuropsychiatric and neurodegenerative diseases, but its genetic architecture is poorly understood. Here, we identified 17 unique genome-wide significant loci and 161 candidate genes linked to the ALPS-indexes in a discovery sample of 31,021 individuals from the UK Biobank. Seven loci were replicated in two independent datasets. Genetic signals located at the 2p23.3 locus yielded significantly concordant effects in both young and aging cohorts. Genetic correlation and polygenic overlap analyses indicate a common underlying genetic mechanism between the ALPS-index, ventricular volumes, and cerebrospinal fluid tau levels, with GMNC (3q28) and C16orf95 (16q24.2) as the shared genetic basis. Our findings enhance the understanding of the genetics of the ALPS-index and provide insight for further research into the neurobiological mechanisms of glymphatic clearance activity across the lifespan and its relation to neuropsychiatric phenotypes.